2021
DOI: 10.1038/s41590-021-00913-5
|View full text |Cite
|
Sign up to set email alerts
|

Microglia use TAM receptors to detect and engulf amyloid β plaques

Abstract: Two microglial TAM receptor tyrosine kinases - Axl and Mer - have been linked to Alzheimer’s disease, but their roles in disease have not been tested experimentally. We find that in Alzheimer’s disease and its mouse models, induced expression of Axl and Mer in amyloid plaque-associated microglia was coupled to induced plaque decoration by the TAM ligand Gas6 and its co-ligand phosphatidylserine. In the APP/PS1 mouse model of Alzheimer’s disease, genetic ablation of Axl and Mer resulted i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

21
274
0
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 299 publications
(297 citation statements)
references
References 61 publications
21
274
0
2
Order By: Relevance
“…Indeed, recent studies demonstrated that sustained depletion of microglia in the 5XFAD model impaired plaque development, revealing a central role of reactive microglia in genesis of Aβ plaques ( 43 ). Moreover, microglia were found to promote dense-core plaques via phagocytic uptake of loosely organized Aβ and condensing it into dense deposits in lysosomes ( 53 ). It would be interesting to test whether the reactive phenotypes acquired by glia as a result of multiple exposures to HSV-1, or by recurrent reactivation of latent infections, are similar to those observed in late-onset AD.…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, recent studies demonstrated that sustained depletion of microglia in the 5XFAD model impaired plaque development, revealing a central role of reactive microglia in genesis of Aβ plaques ( 43 ). Moreover, microglia were found to promote dense-core plaques via phagocytic uptake of loosely organized Aβ and condensing it into dense deposits in lysosomes ( 53 ). It would be interesting to test whether the reactive phenotypes acquired by glia as a result of multiple exposures to HSV-1, or by recurrent reactivation of latent infections, are similar to those observed in late-onset AD.…”
Section: Discussionmentioning
confidence: 99%
“…Progressive accumulation of amyloid-β (Aβ) in form of extracellular plaques along with intracellular deposition of hyperphosphorylated tau protein in neurofibrillary tangles (NFT) are classical pathological hallmarks of Alzheimer's disease (AD) (d 'Errico & Meyer-Luehmann, 2020;Haass & Selkoe, 2007;Hyman et al, 2012;Selkoe & Hardy, 2016). Aβ deposits can also be detected intracellularly, particularly inside of neurons (Gouras et al, 2010;Gouras et al, 2012;Kumar et al, 2013;Wirths et al, 2009) and within the vasculature of the brain (Huang et al, 2021;Spangenberg et al, 2019;Thal et al, 2008;Thal et al, 2009). Aβ peptides can undergo post-translational modifications that alter aggregation and neurotoxic characteristics and might thereby modulate the pathogenesis of AD (Barykin et al, 2017;Kummer & Heneka, 2014).…”
Section: Introductionmentioning
confidence: 99%
“…The TAM receptor family has been reported to play a role in regulating microglial phagocytosis ( Fourgeaud et al, 2016 ; Butovsky and Weiner, 2018 ; Burstyn-Cohen and Hochberg, 2021 ; Huang et al, 2021 ). Canonical TAMR ligands such as Gas6 and Protein S bind TAM receptors through the C-terminal region and phosphatidylserine via the N-terminal region, bridging TAM expressing cells with phagocytic targets such as apoptotic bodies ( Lemke and Rothlin, 2008 ).…”
Section: Resultsmentioning
confidence: 99%